2017
DOI: 10.1093/ndt/gfx218
|View full text |Cite
|
Sign up to set email alerts
|

The reduction of heparan sulphate in the glomerular basement membrane does not augment urinary albumin excretion

Abstract: The reduction of HSPG in the GBM did not augment urinary albumin excretion. HSPG's anionic charge appears to contribute little to the glomerular charge barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Their water and diet were available randomly. The mice were weaned at 4 weeks of age and were thereafter fed with high protein/ high calorie diet for 10 weeks in order to apply a load to the kidney [15]. WT (n = 7) and iNOS-TG (n = 4) mice were sacrificed at their 14 weeks of age.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Their water and diet were available randomly. The mice were weaned at 4 weeks of age and were thereafter fed with high protein/ high calorie diet for 10 weeks in order to apply a load to the kidney [15]. WT (n = 7) and iNOS-TG (n = 4) mice were sacrificed at their 14 weeks of age.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Here it is primarily found as part of the proteoglycan, agrin [59,60]. Whether GBM HS plays a role in protein restriction is under debate [59,[61][62][63], although a general note for these and all Glx studies is that there is a need to discriminate between GAG of eGlx and elsewhere (i.e GBM, podocytes and mesangial cells).…”
Section: Glomerular Eglxmentioning
confidence: 99%
“…By the other hand, it is known that HSPGs are abundant in the glomerular basal membrane and it has been thought to play a major role in the charge-selective glomerular filtration barrier. However, knockout of Ext3 (an enzyme that adds GlcNAc to the fixed tetrasaccharides on the core protein in proteoglycans) in podocytes and glomerular basal membrane did not lead to overt proteinuria ( Aoki et al, 2018 ). Aoki et al (2018) found a bumpy glomerular basal membrane and podocyte effacement by electron microscopy using a Extl3KO mice model compared with Diabetes Mellitus and high sodium intake mice groups, however they had some limitations in their study because the follow-up period was too short for remarkable renal impairments and establishment of hypertension.…”
Section: The Glomerular Endothelial Glycocalyx Is a Barrier That Is Smentioning
confidence: 99%
“…However, knockout of Ext3 (an enzyme that adds GlcNAc to the fixed tetrasaccharides on the core protein in proteoglycans) in podocytes and glomerular basal membrane did not lead to overt proteinuria ( Aoki et al, 2018 ). Aoki et al (2018) found a bumpy glomerular basal membrane and podocyte effacement by electron microscopy using a Extl3KO mice model compared with Diabetes Mellitus and high sodium intake mice groups, however they had some limitations in their study because the follow-up period was too short for remarkable renal impairments and establishment of hypertension. Additionally, renal function tests and HS urine measurements were not assessed in all groups of mice, which would help to support the possible role of HSPGs in the physiology of the GFB.…”
Section: The Glomerular Endothelial Glycocalyx Is a Barrier That Is Smentioning
confidence: 99%